Mapping Guidelines for Preserving Built Heritage: An Essay on the Central Station of Brazil (JF / MG) - Almeida, Karla Carvalho de; Souza, Rosiane de Oliveira; Jacques, Fabiana Mendes Tavares (Technical and Scientific Journal Green Cities, 2022)
This article aims to demonstrate the importance of preserving and adequately restoring the built heritage for the landscape of the city in which it is located. It indicates, in a simplified way, guidelines on how to perform a mapping on building damage. The result is a documentation that thoroughly analyzes the pathologies found in a historical construction, their possible causes and how to treat them so that there is no historical loss; in order to guide restoration professionals and related areas, assisting in the perception, study and future preservation of historic buildings. The study was carried out through a mapping carried out in loco at the Central do Brasil Station, located in the city of Juiz de Fora, Minas Gerais, which houses an art school. The place has great relevance in several aspects for the city, mainly for the perception of local identity, although it is currently in a moderate state of disintegration. KEYWORDS: Preservation. Damage mapping. Patrimony.